2009
DOI: 10.1007/s11199-009-9681-x
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy as Viewed by Mexican Women and Men

Abstract: This study explored the views of Mexican men and women concerning hysterectomy. We studied 120 women and 135 men between the ages of 36 and 55. Women had not had a hysterectomy and men were married to a woman without a hysterectomy. The most negative views about hysterectomy were women's suppositions about male perceptions, but only among people with a limited educational background. This group was more likely to believe that women who undergo hysterectomy are incomplete, rejected by their partners, and experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
6

Year Published

2012
2012
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
1
5
0
6
Order By: Relevance
“…Furthermore, the results also showed that participants who had less schooling held the most negative attitudes toward hysterectomy, a finding that is consistent with a previous study conducted in Mexico in which it was found that people with limited education have more negative views about hysterectomy than do people with higher education (Marván et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Furthermore, the results also showed that participants who had less schooling held the most negative attitudes toward hysterectomy, a finding that is consistent with a previous study conducted in Mexico in which it was found that people with limited education have more negative views about hysterectomy than do people with higher education (Marván et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…Some women have so thoroughly learned and reinforced these concepts of the feminine role that they become excessively anxious about a surgical procedure-such as hysterectomy-that even symbolically threatens that role (Williams, 1980). This is particularly important since the uterus has been discursively constructed as denoting female sexuality and femininity and therefore its absence usually produces concerns about feminity and sexual functioning (Dell & Papagiannidou, 1999;Marván et al, 2009;Reis et al, 2008). In a study in which Mexican American and Caucasian women were asked what they had heard about the effects of hysterectomy prior to undergoing the surgery themselves, there were more Mexican Americans who had heard they were going to experience a change for the worse in their experience of intercourse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…El miedo ha sido descrito previamente por otros autores en otros países (23). En este estudio, el miedo por un lado se asocia al evento quirúrgico propiamente tal, por otro y con más fuerza se presenta asociado a las consecuencias de la cirugía (14,26). Augustus (17), en un estudio etnográfico encontró, al igual que este estudio, que el miedo de la mujer se relaciona al funcionamiento sexual postoperatorio.…”
Section: Discussionunclassified